(untitled) (Journal of Medicine, 2013)
Background: Tuberculosis (TB) is a major cause of mortality and is affecting millions of people in third world countries. In DOTS patients are monitored facility based and treatment supporter based; by these two ways patients are observed for the treatment. The aim of the study was to explore the role of treatment supporters and their impact on the treatment outcomes. Material and Method: The study was a cross-sectional survey within routine TB control program operational context. All sputum smear positive TB patients diagnosed, registered in public sector, urban and rural diagnostic centre during year 2008 with available outcomes were included in the study. Data was collected during August- October 2010 from 15 health facilities of 451 patients. Results: The majority of the patients (89.6%) were provided with treatment supporters. In 404 (89.6%) cases in which treatment supporters were provided, 203 (50.2%) were lady health worker, 46 (11.4%) were community health worker and health facility worker, and 155 (38.4%) were family member and community volunteer. 384 (85.1%) were categorized as treatment success, 31 (6.9%), as transferred out, 17 (3.8%), as dead, 16 (3.5%) as defaulted and three (0.7%) as treatment failure. The treatment success rates in patients supervised by lady health worker, community health worker and health facility worker, and family member and community volunteer was 93.1%, 89.1% and 73.5%, respectively. Conclusions: We found a significantly higher treatment success (93.1%) in patients supervised by lady health workers compared to other types of treatment support. The overall treatment success rate was 85.1%. DOI: http://dx.doi.org/10.3329/jom.v14i1.14535 J MEDICINE 2013; 14 : 40-46